Analisis Pemindahan Pusat Administrasi Pemerintahan Kabupaten Aceh Utara terhadap Pelayanan Publik - Pocut Navieza; Zahratul Idami; Helmi Helmi (Journal of Social and Policy Issues, 2021)
Based on the Regulation of Republic of Indonesia Government No. 18 of 2003 concerning the Transfer of the Capital of North Aceh Regency from Lhokseumawe to Lhoksukon, thus it need to be moved immediately. However, the transfer of the administrative center of North Aceh Regency from Lhokseumawe to Lhoksukon was not optimal and had a negative impact on the slow access to public services, negative development of economic growth, and hindered development of North Aceh Regency itself. This study aims to determine and explain the cause of the delay in moving the Administrative Center of North Aceh Regency from Lhokseumawe City to Lhoksukon City. Method in this research uses a qualitative study with descriptive approach. The data were obtained from the results of field research based on observations, interviews with relevant informants, documentation, and literature. The theory used in this research is the theory of public administration and public service. The results showed the delay in moving the Government Administrative Center of North Aceh Regency due to the absence of supporting tools for public services, limited budget allocations, and the political reasons for controlling the assets of North Aceh Regency in Lhokseumawe City. Then the process of implementing the transfer of the Regional Work Unit (RWU) to date from 26 RWU, only 6 RWU which have been moved to Lhoksukon, and this has resulted in the inefficiency of services provision. It is recommended that the North Aceh government in providing public services to the community must prioritize good public service standards in accordance with the principles of good and right public services. In providing services, the government as the service provider must prioritize the public interest and not make the excuse that there is no means of supporting public services as an obstacle to the ongoing process of public service. Then it is expected that regional governments increase budget allocations to meet the needs of moving the administrative center of North Aceh Regency. As well as immediately transferring assets so that Government Regulation No. 18 of 2003 can be fulfilled.